Circulations in the global history of art - Dossin, Catherine; Joyeux-Prunel, Béatrice; Kaufmann, Thomas DaCosta (Studies in art historiography, 2016)
1. Reflections on world art history / Thomas DaCosta Kaufmann -- 2. Art history and Iberian worldwide diffusion : Westernization/globalization/Americanization / Serge Gruzinski -- 3. Circulation and beyond : the trajectories of vision in early modern Eurasia / Monica Juneja -- 4. Circulations : early modern architecture in the Polish-Lithuanian borderland / Carolyn C. Guile -- 5. Cultural transfers in art history / Michel Espagne -- 6. Spatial translation and temporal discordance : modes of cultural circulation and internationalization in Europe (second half of the nineteenth and first half of the twentieth century) / Christophe Charle -- 7. Mapping cultural exchange : Latin American artists in Parish between the wars / Michele Greet -- 8. The global NETwork : an approach to comparative art history / Piotr Piotrowski -- 9. Global conceptualism? Cartographies of conceptual art in pursuit of decentering / Sophie Cras -- 10. The German century? How a geopolitical approach could transform the history of modernism / Catherine Dossin and Beatrice Joyeux-Prunel.